Factors Affecting the Livelihood Diversification of Rice Farming Households in Deli Serdang Regency - Sianipar, Kristin Sion; Pakpahan, Helena Tatcher; Nababan, Manaor Bismar Posman (JSEP (Journal of Social and Agricultural Economics), 2023)
Deli Serdang Regency is the leading rice producer in North Sumatra Province. The fact is that productivity in Deli Serdang Regency has stagnated. The problems farmers face isclimate change, access to irrigation, and rising input prices. This study aimed to determine the income of rice farmers, the percentage level of farmers doing livelihood diversification, and the variables that influence livelihood diversification. Four hundred people (especially rice farmers) became the research sample. The data analysis method is Multinomial Logit Analysis. The results of this study indicate that the average income is 1,221,680.5/month. The income of these rice farmers is below the Deli Serdang UMK. Then, our study found that 67% of rice farmers diversified their livelihoods. Finally, the results of our study show that the variables that have an essential influence on livelihood diversification in Deli Serdang Regency are land area, dependency ratio, counseling, membership of farmer groups, distance to markets, and farming experience.